Misa Lingkungan yang Berdaya Ubah Bagi Persaudaraan Umat Beriman Menurut Kevin W. Irwin dan Paus Yohanes Paulus II : Studi kasus di Paroki Santo Aloysius Gonzaga, Mlati, Keuskupan Agung Semarang - Yosafat Elly Dhita Karunia (Media (Jurnal Filsafat dan Teologi), 2021)
This article aims at examining the effects of misa lingkungan on the ecclesial life of parishioners. The question is whether misa lingkungan has any transformative power for building a communion of parishioners? As a theoretical concept, the author takes some ideas developed by Kevin W. Irwin in his book Models of the Eucharist, as well as some of the main ideas of Pope John Paul II's encyclical Ecclesia de Eucharistica. Based on these theological concepts, the author conducted interviews and questionnaires aimed at the parishioners of St. Aloysius Gozaga Parish, Mlati, Semarang Archdiocese. He tries to find out how far the adage lex orandi – lex credendi – lex vivendi influenced the understanding and the living of the parishioners. The author concludes that the Eucharist that is believed, lived, and celebrated has a positive impact on parishioners. The fruits of the Eucharist celebration were seen in their spirit of brotherhood and solidarity for those in need.